Seismic Vulnerability Assessment Form for Free-Standing Columns Based on a Simplified Numerical Analysis. Issue 2 (2nd April 2016) - Pappas, Athanasios; da Porto, Francesca; Modena, Claudio
ABSTRACT: This article describes the creation of a seismic vulnerability assessment form for free-standing columns, based on Discrete Element Method simulations. A broad range of column configurations, selected after archaeological research, was analyzed. Each soil-column configuration was tested with 56 artificial accelerograms in the range of peak ground acceleration between 0.2 and 0.8 g. Fragility curves were created for each configuration and used to quantify the effects of soil, and the slenderness, height, and number of drums of each column. The influence factors of all parameters were used in the assessment form to categorize the columns into vulnerability classes, according to their probability of collapsing when subjected to a certain level of seismic excitation. The proposed tool can be used for rapid, preliminary, seismic vulnerability assessment, without the need for further sophisticated calculations. Four ancient columns, which have survived earthquakes of known acceleration amplitude, were used to apply, test and validate the proposed assessment form.